A Bilingual Speech Analysis in The Makna Talks Podcast Episode Featuring Nicholas Saputra - Fatan Ariful Ulum; Malikatul Laila (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze bilingual speech in a selected episode of the Makna Talks podcast featuring Nicholas Saputra. It focuses on identifying types of bilingualism-compound, coordinate, and subordinate-based on Weinreich and Martinet's (2010) framework and explaining how these bilingual patterns function within conversational discourse.Methodology: This study employs a descriptive qualitative approach. Eighteen utterances containing Indonesian–English language alternation were collected by observing and transcribing the selected podcast episode. The utterances were identified, classified, and analyzed according to Weinreich and Martinet's typology of bilingualism. Relevant theories and previous studies were also reviewed to support interpretation.Results: The findings show that only two types of bilingualism appear in the data: compound and coordinate bilingualism. Compound bilingualism is the dominant type, occurring in 14 utterances (77.8%), indicating an integrated use of Indonesian and English within the same units of meaning. Coordinate bilingualism appears in 4 utterances (22.2%), mainly in contexts involving quotations or discourse framing.Applications/Originality/Value: This study contributes to sociolinguistic research by demonstrating how bilingual speech operates in informal podcast discourse. It highlights bilingualism as a communicative strategy for identity construction, audience engagement, and media performance in contemporary Indonesian digital contexts.